2018
DOI: 10.3390/asi1030026
|View full text |Cite
|
Sign up to set email alerts
|

A System for Controlling and Monitoring IoT Applications

Abstract: In this work, the design and implementation of an open source software and hardware system for Internet of Things (IoT) applications is presented. This system permits the remote monitoring of supplied data from sensors and webcams and the control of different devices such as actuators, servomotors and LEDs. The parameters which have been monitored are brightness, temperature and relative humidity all of which constitute possible environmental factors. The control and monitoring of the installation is realised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…First, the IoT-based sensor device developed in this study is based on Raspberry Pi which is small-size, low-cost, and powerful single-board computer device. Previous studies have shown significant advantages of utilizing Raspberry Pi such as for controlling and monitoring IoT system [ 83 ], estimating the roll angle of a vehicle using embedded neural network in real-time [ 84 ], hosting and serving the user interface of eHealth care system [ 59 ], and monitoring the temperature of lava lake using near infrared thermal camera [ 85 ]. Therefore, the proposed IoT-based sensor device developed in this study could be applied to monitor the manufacturing process in real-time.…”
Section: Resultsmentioning
confidence: 99%
“…First, the IoT-based sensor device developed in this study is based on Raspberry Pi which is small-size, low-cost, and powerful single-board computer device. Previous studies have shown significant advantages of utilizing Raspberry Pi such as for controlling and monitoring IoT system [ 83 ], estimating the roll angle of a vehicle using embedded neural network in real-time [ 84 ], hosting and serving the user interface of eHealth care system [ 59 ], and monitoring the temperature of lava lake using near infrared thermal camera [ 85 ]. Therefore, the proposed IoT-based sensor device developed in this study could be applied to monitor the manufacturing process in real-time.…”
Section: Resultsmentioning
confidence: 99%
“…The following in Figure 6 is a design form of the existing microcontroller or hardware firmware and an explanation of the program syntax flow with pseudocode as shown in Algorithm 1. The microcomputer module is a mini computer connecting the microprocessor and main memory as an inputoutput interface [29]. This study uses a Raspberry Pi Model 4 microcomputer; this computer board is installed with a Linux-based operating system and is used as a core processing device that serves as an IoT Broker and Apache web service.…”
Section: The Electrical Hardware Designsmentioning
confidence: 99%
“…Raspberry Pi and other single-board computers are low-cost development devices for testing and education [11]. Raspberry Pi operates on the Raspbian Operating System (OS) that is based on Debian (Linux) [12]. Operating on the Raspbian OS enables Raspberry Pi to have access to multiple packages and programs such as the Python programming language that is widely used in machine learning and deployment development.…”
Section: Raspberry Pi Fig3 Layout Of Raspberry Pimentioning
confidence: 99%